Characterization of bacteriocin produced by Lactococcus lactis subsp. lactis S20 isolated from chinese Sauerkraut and its antilisterial activity In milk - Chin, Yih Zhet (2016)
Chemical preservatives might cause negative side-effects to public health. Much research have been done for searching natural preservatives to cope with the heightened public awareness. Therefore, the objective of this study is to characterize the bacteriocin isolated from traditional pickled vegetable and to evaluate its antilisterial activity in milk. Among the four traditional pickled vegetables studied, only Chinese sauerkrauts (suan cai) showed the presence of LAB with an average LAB count of 6.73 × 106 CFU/g. Lactococcus lactis subsp. lactis S20, a bacteriocinogenic lactic acid bacterium, was isolated from Chinese sauerkraut. This strain produced the highest bacteriocin activity (1280 AU/ml) against Listeria monocytogenes ATCC 19115 after 20 h of culture at 30°C in MRS broth, although results in this study demonstrate that TSB was a suitable alternative bacteriocin production medium. The quantification of bacteriocin activity was determined by using microtiter plate assay. L. lactis subsp. lactis S20 displayed the ability to ferment sucrose and xylose which are uncommon to L. lactis. Bacteriocin S20 exhibited inhibitory activity against most Gram-positive food pathogens but did not inhibit the growth of Gram-negative bacteria. Results of the stability tests indicate that bacteriocin S20 was resistant to trypsin, amylase, and lipase but sensitive to proteinase K, α-chymotrypsin, and pepsin. This bacteriocin was stable over a wide range of pH (pH 3-9) and at temperatures of up to 70°C for 15 min. The bacteriocin activity of bacteriocin S20 dropped to 40 AU/ml after autoclaving at 121°C for 15 min. Taken together, the results from the stability tests and molecular studies suggest that bacteriocin S20 is closely related to nisin A. The extraction of bacteriocin S20 was conducted by using the cell-adsorption method. Based on the bacteriocin adsorption study, pH 6 and pH 7 were the optimal pH for the adsorption of bacteriocin S20. The cells of the sensitive strain showed a higher adsorption of bacteriocin S20 than did the producer strain. Bacteriocin adsorption in the general medium TSB was relatively higher than that in MRS. Conversely, higher recovery yield and fold of purification were observed in bacteriocin S20 extracted from MRS. Bacteriocin S20 has shown to effectively control Listeria cells in milk system (UHT milk). After initially reduced by the bacteriocin S20, the Listeria counts remained almost constant throughout the 14 days of storage. Results also revealed that Listeria count of milk samples with 320 AU/ml bacteriocin S20 had little or no significant difference (p>0.05) to that of 160 AU/ml. In addition, bacteriocin S20 showed an effective antilisterial activity in skim milk containing <12% (w/v) milk solids-not-fat (MSNF). MSNF might interact with bacteriocin S20 and affect its antimicrobial activity in milk. In conclusion, bacteriocin S20 that have been successfully isolated from Chinese sauerkraut have a potential to be used as antilisterial in food.